Categorical Frailty Phenotype and Continuous Frailty Index: A Conceptual Overview of Frailty and Its Components among Older Persons in India (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Frailty indicator can be an important indicator of understanding ageing and health in India. It will be interesting to examine and compared different model of frailty using the same dataset. The present paper aimed to compare two frailty models and examine the association between socioeconomic status with frailty and frailty components among older persons in India. Methods: The WHO Study on Global AGEing and Adult Health (SAGE) Wave 1, collected between 2007 and 2010 in India was used for this study. Two frailty model was constructed. Education and wealth quintile was used as socio economic indicators. Sensitivity and specificity were calculated for comparing both frailty models. Linear regression and logistic regression were used. The regression analysis was separately done for each age group and gender category. The coefficients were reported separately for education and wealth quintile categories. Results: Low sensitivity was observed between the two frailty models. The results suggest that frailty index was more useful in depicting wealth and education inequality among different gender and age groups in India. Wealth and education differences in, number of morbidities, morbidity symptoms and Self rated health (SRH) were most consistently significant across age groups and gender categories. BMI and functional limitation were even found significant at p-value